2022
DOI: 10.3349/ymj.2022.63.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cerebro-Cardiovascular Diseases among Police Officers and Firefighters: A Nationwide Retrospective Cohort Study

Abstract: Purpose Police officers and firefighters are exposed to risk factors for cerebro-cardiovascular diseases, and the actual risk is expected to increase compared with other occupational groups. The present study aimed to estimate the risks of cerebro-cardiovascular diseases in police officers and firefighters compared to other occupational groups. Materials and Methods Using the National Health Insurance Service data, we constructed a retrospective cohort of public officer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Our findings align with previous studies that showed a high prevalence of CVD and CVD-related mortality in police officers [ 2 , 4 ]. In particular, our study highlighted its association with age and hypertension status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings align with previous studies that showed a high prevalence of CVD and CVD-related mortality in police officers [ 2 , 4 ]. In particular, our study highlighted its association with age and hypertension status.…”
Section: Discussionsupporting
confidence: 93%
“…Police officers face various health issues that influence their overall well-being, including an elevated risk of developing cerebro-cardiovascular diseases (CVD) [ 1 4 ]. A population-based study in the Republic of Korea showed that police officers had a significantly higher risk of developing angina pectoris (1.5 times higher), cerebrovascular disease (1.4 times higher), and acute myocardial infarction (1.8 times higher) compared with other government workers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, statistics reported by the National Law Enforcement Officers Memorial Fund show that, in 2020, 295 LEO’s died while on duty in the United States (National Law Enforcement Officers Memorial Fund, 2021). In addition to these operational risks, other detrimental health outcomes including cardiovascular diseases and related risk factors have been associated with law enforcement (Gendron et al, 2019; Lee et al, 2022; Rostami et al, 2019; Violanti, 2014). Previous studies also report that (LEO’s) suffer from chronic pain, including back pain (Benyamina Douma et al, 2017; Carleton et al, 2017) and have a higher incidence of mental health problems compared with the general population (MacEachern et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…5 The NHIS provides a free health screening program that is conducted biennially for all insured individuals living in Korea. 6 The National Health Insurance Service-National Health Screening Cohort data consisted of 514 795 individuals, comprising a random sample of ≈10% of all eligible Korean adults aged 40 to 79 years who underwent health screening in 2002 or 2003. The database contained information regarding participants’ health screening examinations between 2002 and 2019, such as demographic characteristics, anthropometric measurements, laboratory test results of blood and urine, and questionnaires on health behaviors, including smoking habits.…”
Section: Methodsmentioning
confidence: 99%